Effects of 5-ion 6-beam sequential irradiation in the presence and absence of hindlimb or control hindlimb unloading on behavioral performances and plasma metabolic pathways of Fischer 344 rats - Raber, Jacob; Chaudhari, Mitali; De la Torre, Alexis; Holden, Sarah; Kessler, Kat; Glaeser, Breanna; Lenarczyk, Marek; Leonard, Scott Willem; Borg, Alexander; Kwok, Andy; Patel, Chirayu; Kronenberg, Amy; et al. (Frontiers in Physiology, 2024)
Effects and interactions between different spaceflight stressors are expected to be encountered by crew on missions, where microgravity and exposure to galactic cosmic rays (GCR) will occur. A limitation of previous studies of simulated weightlessness using hindlimb unloading (HU) is that a control HU condition was not included. We characterized the behavioral performance of male Fischer rats 2 months after shamirradiation or total body irradiation with a simplified 5-ion mixed beam exposure representative of the GCR in the absence or presence of HU. Six months later, plasma, hippocampus, and cortex were processed to determine whether the behavioral effects were associated with long-term alterations in metabolic pathways. In the open field without and with objects, there was a radiation x HU interaction. In plasma of animals that did not receive HU or the HU control condition, the Riboflavin metabolism pathway was mostly affected, comparing sham-irradiation versus 0.75 Gy. When in sham-irradiated animals the effects of control HU on plasma were analyzed, the Alanine, aspartate and glutamate metabolism, Riboflavin metabolism, Arginine biosynthesis, and Glutamine and glutamate metabolism were affected. When in sham-irradiated animals the effects of control HU on the hippocampus were assessed, the Phenylalanine, tyrosine, and tryptophan pathway was most affected. When effects of 0.75 Gy irradiation were analyzed in the cortex of HU control animals, like in the hippocampus, the Glutamine and glutamate metabolism pathway was affected, while in animals that did not receive the HU control condition, the Riboflavin pathway was affected. When in sham-irradiated animals the effects of the control HU condition on the cortex were analyzed, the Riboflavin metabolism pathway was affected. In 0.75 Gy-irradiated animals, the Glutamine and glutamate metabolism pathway was affected, while in 1.5 Gy-irradiated animals, the Riboflavin metabolism pathway was affected. There were 21 plasma metabolites that correlated with behavioral measures, indicating that plasma and brain biomarkers associated with behavioral performance are dependent on the environmental condition(s) experienced.Phenylalanine, tyrosine, and tryptophane metabolism and the metabolites phenylalanine and tryptophane in plasma are biomarkers to consider for spaceflights, as they were revealed in both Fischer and WAG/Rij rats exposed to simGCR and/or HU.